الجانب الإجتماعي في حیاة النبيﷺ قبل البعثة من خلال کتاب عیون الأثر: The Social Aspect of The Prophet’s Life Before Prophethood Through the Book "Uyoon-Al-Athar" - Atta Ullah Subhani; Dr. Yousef Muhammad Tahir (Al Manhal Research Journal, 2024)
Uyoon al-Athar" is a distinguished work on the Seerah (biography) of the last Prophet of Allah, Muhammad (peace be upon him), authored by Ibn Sayyid al-Nas. Written in Arabic, the book showcases exceptional literary and grammatical qualities, making it a masterpiece of Seerah literature. This study delves into the life of Ibn Sayyid al-Nas, the historian behind this significant work, focusing on the historical context of the Mamluk period (648 AH/1250 AD - 923 AH/1517 AD), during which the Mamluks ruled Egypt. The Mamluk rulers encouraged scholars of their time to compose historical works, particularly biographies of the Prophet. This article comprehensively explores the methodology and style adopted by Ibn Sayyid al-Nas in writing the Seerah, with special attention to his unique approach to the Maccan period, which set him apart from earlier historians of the Prophet’s biography.